Theory of Optimal Design of Construction - Alamkhon Turdalievich Saidmamatov (Genius Journals, 2022)
The article describes the analysis of the theory and optimal design of the structure, the analysis and selection of a constructive solution, analyzes the technical and economic indicators of various design solutions.
Keywords: Optimization Of Building Structures; Criteria Of Optimality; Consumption Of Materials; Building Cost